Increasing use of immunotherapy and prolonged survival among younger patients with primary CNS lymphoma: a population-based study. (3rd July 2019) - Neuhauser, Magdalena; Roetzer, Thomas; Oberndorfer, Stefan; Kitzwoegerer, Melitta; Payer, Franz; Unterluggauer, Julia J.; Haybaeck, Johannes; Stockhammer, Günther; Iglseder, Sarah; Moser, Patrizia; Thomé, Claudius; Stultschnig, Martin; et al.
Abstract: Background: Primary CNS lymphoma is a highly aggressive and rare type of extranodal non-Hodgkin lymphoma. Although, new therapeutic approaches have led to improved survival, the management of the disease poses a challenge, practice patterns vary across institutions and countries, and remain ill-defined for vulnerable patient subgroups. Material and Methods: Using information from the Austrian Brain Tumor Registry we followed a population-based cohort of 189 patients newly diagnosed from 2005 to 2010 through various lines of treatment until death or last follow-up (12-31-2016). Prognostic factors and treatment-related data were integrated in a comprehensive survival analysis including conditional survival estimates. Results: We find variable patterns of first-line treatment with increasing use of rituximab and high-dose methotrexate (HDMTX)-based poly-chemotherapy after 2007, paralleled by an increase in median overall survival restricted to patients aged below 70 years. In the entire cohort, 5-year overall survival was 24.4% while 5-year conditional survival increased with every year postdiagnosis. Conclusion: In conclusion, we show that the use of poly-chemotherapy and immunotherapy has disseminated to community practice to a fair extent and survival has increased over time at least in younger patients. Annually increasing conditional survival rates provide clinicians with an adequate and encouraging prognostic measure.